2004
DOI: 10.1079/bjn20031016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a high-protein, high-sodium diet on calcium and bone metabolism in postmenopausal women and its interaction with vitamin D receptor genotype

Abstract: The influence of a high-Na, high-protein (calciuric) diet on Ca and bone metabolism was investigated in postmenopausal women (aged 50 -67 years) who were stratified by vitamin D receptor (VDR) genotype. In a crossover trial, twenty-four women were randomly assigned to a diet high in protein (90 g/d) and Na (180 mmol/d) or a diet adequate in protein (70 g/d) and low in Na (65 mmol/d) for 4 weeks, followed by crossover to the alternative dietary regimen for a further 4 weeks. Dietary Ca intake was maintained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 58 publications
1
21
1
1
Order By: Relevance
“…Urinary NTx excretion was about 25% higher in postmenopausal women in the ÀHRT group when consuming the calciuric diet compared to basal diet, whereas there was no change in urinary NTx in women in the þ HRT group. While there are no comparable human data in the literature on the combined effect of increased Na and protein intake on markers of bone resorption in postmenopausal women on HRT, we have recently reported a comparable increase in urinary NTx/creatinine levels (B19%) in response to increased dietary Na and protein in postmenopausal women not taking HRT (Harrington et al, 2004). In addition, increased Na intake has been reported to increase markers of bone resorption (urinary DPD (Evans et al, 1997) and NTx (Sellmeyer et al, 2002)) in two out of the three published crossover intervention studies in postmenopausal women not receiving HRT (Evans et al, 1997;Lietz et al, 1997;Sellmeyer et al, 2002; for a review, see Cashman & Flynn, 2003).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Urinary NTx excretion was about 25% higher in postmenopausal women in the ÀHRT group when consuming the calciuric diet compared to basal diet, whereas there was no change in urinary NTx in women in the þ HRT group. While there are no comparable human data in the literature on the combined effect of increased Na and protein intake on markers of bone resorption in postmenopausal women on HRT, we have recently reported a comparable increase in urinary NTx/creatinine levels (B19%) in response to increased dietary Na and protein in postmenopausal women not taking HRT (Harrington et al, 2004). In addition, increased Na intake has been reported to increase markers of bone resorption (urinary DPD (Evans et al, 1997) and NTx (Sellmeyer et al, 2002)) in two out of the three published crossover intervention studies in postmenopausal women not receiving HRT (Evans et al, 1997;Lietz et al, 1997;Sellmeyer et al, 2002; for a review, see Cashman & Flynn, 2003).…”
Section: Discussionmentioning
confidence: 49%
“…Women in the þ HRT and ÀHRT groups were randomly assigned to the calciuric diet (ie, high in Na (180 mmol/day) and protein (90 g/day)) or the basal diet (ie, adequate in protein (70 g/ day) and low in Na (65 mmol/day)) for 4 weeks, followed by crossover to the alternative dietary regimen for a further 4 weeks. Information on the calciuric diet as well as the methodology for assessment of urinary NTx, Ca, Na, potassium (K), nitrogen (N), serum bone-specific alkaline phosphatase, osteocalcin, 25-hydroxyvitamin D (25 OH D 3 ) or 1,25-dihydroxyvitamin D (1,25 (OH) 2 D 3 ) and plasma parathyroid hormone (PTH) levels are described in detail elsewhere (Harrington et al, 2004).…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Study compliance was 98% using a pill count and was also measured by the incorporation of the cis-9,trans-11 isomer of CLA into total plasma lipids. The duration of the intervention (8 weeks) was chosen on the basis that most of the studies that have investigated the effect of CLA on body composition, plasma lipids, and glucose, insulin and/or leptin levels (see review by Terpstra, 2004) were of 4-12 weeks in duration, together with the fact that we and others have shown that levels of biochemical markers of bone turnover can be altered by dietary intervention/supplementation in as little as 2-4 weeks (Ginty et al, 1998a, b;Lin et al, 2003;Harrington et al, 2004).…”
Section: Designmentioning
confidence: 99%
“…Rapuri et al [23] showed that postmenopausal women with the tt genetic variant of VDR appeared to be at a greater risk for the deleterious effect of a high caffeine intake ([300 mg/d) on vertebral bone loss over 3 years, compared to women with the TT VDR genotype. Harrington et al [24] recently showed an interaction between VDR genotype and the effect of a high sodium-high protein intake on the rate of bone resorption in postmenopausal women.…”
Section: Vitamin D Receptor Genotype-cholecalciferol Interactionsmentioning
confidence: 99%